Harnessing the Immunomodulatory Properties of Bacterial Ghosts to Boost the Anti-mycobacterial Protective Immunity - Lim, Jieling; Koh, Vanessa Hui Qi; Cho, Sharol Su Lei; Periaswamy, Balamurugan; Choi, Dawn Poh Sum; Vacca, Maurizio; De Sessions, Paola Florez; Kudela, Pavol; Lubitz, Werner; Pastorin, Giorgia; Alonso, Sylvie (Frontiers in Immunology, 2019)
Tuberculosis (TB) pathogenesis is characterized by inadequate immune cell activation and delayed T cell response in the host. Recent immunotherapeutic efforts have been directed at stimulating innate immunity and enhancing interactions between antigen presenting cells and T cells subsets to improve the protective immunity against TB. In this study, we investigated the immunostimulatory properties of bacterial ghosts (BG) as a novel approach to potentiate the host immunity against mycobacterial infection. BG are intact cytoplasm-free Escherichia coli envelopes and have been developed as bacterial vaccines and adjuvant/delivery system in cancer immunotherapy. However, BG have yet to be exploited as immunopotentiators in the context of infectious diseases. Here, we showed that BG are potent inducers of dendritic cells (DC), which led to enhanced T cell proliferation and differentiation into effector cells. BG also induced macrophage activation, which was associated with enhanced nitric oxide production, a key anti-mycobacterial weapon. We further demonstrated that the immunostimulatory capability of BG far exceeds that of LPS and involves both TLR4-dependent and independent pathways. Consistently, BG treatment, but not LPS treatment, reduced the bacterial burden in infected mice, which correlated with increased influx of innate and adaptive effector immune cells and increased production of key cytokines in the lungs. Finally and importantly, enhanced bacilli killing was seen in mice co-administered with BG and second-line TB drugs bedaquiline and delamanid. Overall, this work paves the way for BG as potent immunostimulators that may be harnessed to improve mycobacteria killing at the site of infection.